Optimizing sales force automation system through effective technical support in Pacific Healthcare - Rosapapan, Jennifer R. (Animo Repository, 2017)
Sales Force Automation (SFA) is an information technology tool to automate sales tasks and processes to improve the productivity, efficiency, and effectiveness of sales personnel. This action research focused on the value of equipping the medical sales representatives of Pacific Healthcare (Philippines), Inc. with appropriate technical training on the usage of Sales Force Automation system to fully take advantage of its benefits. As the Business Operations Officer in our company, I led the conduct of two cycles of this action research that centered on training interventions. My colleagues and I designed a Training Program and a Training Manual on Using SFA system to facilitate the technical knowledge transfer to medical sales representatives. The results of the training intervention increased the usage of the Sales Force Automation system and enhanced the productivity of our medical sales representatives. The study noted some implications of automation system in the pharmaceutical context.